Development of the EDL-FET Based Cell Culture Platform for Electrical Cell Proliferation Monitoring. (18th November 2020) - Paulose, Akhil K.; Chen, Po-Hsuan; Lien, Huang-Chun; Wu, Yu-Yi; Chen, Chihchen; Wang, Yu-Lin
Abstract : The pathophysiological changes in cells are mainly focusing on the ionic regulations like hyperpolarization, depolarization etc. The real-time monitoring of these changes in ionic behavior is one of the challenging areas in the biosensor field. A field-effect transistor (FET) based sensor system shows an exceptional advantage in noninvasive real-time monitoring of cellular changes. In this study, we monitored cell proliferation in real-time by using the FET biosensor. Cells were cultured on the FET sensing surface and the potential difference was monitored using the Electric-double-layer field-effect transistor (EDL-FET) biosensor system. Cell proliferation in the sensor surface was electrically measured as drain current change. The impedance measurement changes revealed the capacitive equivalent model of the FETs system. The most important factor in a cell-based system is to overcome the limited life span of cells in sensor platforms. This sensor platform was capable of monitoring cell growth and proliferation, compared with other conventional and current cell sensor platforms. Rapid electrical response corresponding to the cell growth and other functional changes associated with the cell can be used in many fields, including medicine, environmental monitoring and drug screening.